The role of the right temporo–parietal junction in social decision‐making - Bitsch, Florian (Hum Brain Mapp, 2018)
Identifying someone else's noncooperative intentions can prevent exploitation in social interactions. Hence, the inference of another person's mental state might be most pronounced in order to improve social decision‐making. Here, we tested the hypothesis that brain regions associated with Theory of Mind (ToM), particularly the right temporo–parietal junction (rTPJ), show higher neural responses when interacting with a selfish person and that the rTPJ‐activity as well as cooperative tendencies will change over time. We used functional magnetic resonance imaging (fMRI) and a modified prisoner's dilemma game in which 20 participants interacted with three fictive playing partners who behaved according to stable strategies either competitively, cooperatively or randomly during seven interaction blocks. The rTPJ and the posterior–medial prefrontal cortex showed higher activity during the interaction with a competitive compared with a cooperative playing partner. Only the rTPJ showed a high response during an early interaction phase, which preceded participants increase in defective decisions. Enhanced functional connectivity between the rTPJ and the left hippocampus suggests that social cognition and learning processes co‐occur when behavioral adaptation seems beneficial.